Origin of planktotrophy - evidence from early molluscs - Nützel, Alexander; Lehnert, Oliver; Fryda, Jiri (Evolution & Development, 2006)
The size of early ontogenetic shells (protoconchs) of ancient benthic molluscs suggests that feeding larvae occurred at about 490 myr (approximately, transition from Cambrian to Ordovician). Most studied Ordovician protoconchs were smaller than Cambrian ones, indicating smaller Ordovician eggs and hatchlings. This suggests substitution of nutritious reserve matter such as yolk by plankton as an energy source for larvae. The observed size change represents the first direct empiric evidence for a late Cambrian to Ordovician switch to planktotrophy in invertebrate larvae. It corroborates previous hypotheses about a possible polyphyly of planktotrophy. These hypotheses were primarily based on molecular clock data of extant clades with different types of larva, change in the overall body size, as well as increasing predation pressure on Early Paleozoic sea floors. The Early Ordovician is characterized by an explosive radiation of benthic suspension feeders and it was suggested that planktotrophy would prolongate escape from benthic predation on hatchlings. This biological escalation hypothesis does not fully explain why planktotrophy and suspension feeding became important at the same time, during a major biodiversification. An additional factor that probably included availability of nutrients must have played a role. We speculate that an increasing nutrient supply and availability of photoautotrophic plankton in world oceans have facilitated both planktotrophy and suspension feeding, which does not exclude a contemporaneous predation-driven escalation. It is very likely that the evolution of planktotrophy as well as increasing predation contributed to the Ordovician radiation. © 2006 The Author(s).
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IGM.LP.assess_9